Vulvar intraepithelial neoplasia - Caglar, H; Tamer, S; Hreshchyshyn, M M (Obstetrics and gynecology (New York. 1953), 1982)
The authors reviewed the records of 50 patients with carcinoma in situ of the vulva seen at the State University of New York at Buffalo affiliated hospitals. Five patients (10%) were found to be immunosuppressed and 12 (24%) had other preinvasive and invasive genital or extragenital neoplasia. Of 43 patients whose symptomatology was available, almost half (46.5%) were asymptomatic. The most common symptom was vulvar itching in 18 (42%), and 32 (65%) patients had white vulvar lesions. Thirteen patients underwent vulvectomy, 23 underwent wide local excision, 8 underwent skinning and skin graft, 3 underwent topical 5-fluorouracil treatment, and 2 underwent CO2 laser treatment. On follow-up there were 6 patients with recurrent and/or persistent disease. Two recurrences followed wide local excision. Topical 5-fluorouracil failed in all 3 patients and CO2 laser failed in 1 of the 2 underwent laser treatment. There were 5 patients with invasive disease. In 3, diagnostic biopsy failed to reveal invasive neoplasia before surgical excision, and invasion was noted after 5-fluorouracil application in one and after CO2 laser treatment in another. All recurrences responded to therapy. In 41 patients followed up for 3 months to 11 years, there were no cancer-related deaths.